Pelatihan Jaringan Komputer Sebagai Sarana Pembelajaran Di Smk Negeri 2 Empat Lawang - Khairil, Khairil; Sapri, Sapri; Alamsyah, Hendri; Zulfiandy, Ricky (Universitas Dehasen Bengkulu, 2025)
This training aims to enhance students' knowledge of computer networks, providing various benefits in the era of technological advancement. By learning about computer networks, students acquire skills relevant to industry needs, improve digital literacy, and open promising career opportunities. Additionally, this training prepares students for further education. The training was conducted at SMK Negeri 2 Empat Lawang with 46 student participants. The materials covered included fundamental concepts of computer networks, such as protocols, topologies, and network hardware and software. The training was designed using an approach that included delivering materials, simulating the construction of simple computer networks, and evaluation sessions through Q&A to deepen students' understanding. The results of this training showed an increase in students' knowledge, particularly in understanding the basics of computer networks and their ability to assemble and configure simple networks. Moreover, the training successfully fostered students' curiosity and interest in information technology, preparing them to face challenges in the digital era and become individuals ready to compete in the workforce and pursue higher education.